2022
DOI: 10.1101/2022.11.02.22281865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D supplementation improves the prognosis of patients with colorectal cancer liver metastases

Abstract: Colorectal cancer liver metastasis (CRCLM) is one of the deadliest cancers. CRCLM tumours have two distinct histopathological growth patterns (HGPs) including desmoplastic HGP (DHGP) and replacement HGP (RHGP). The DHGP tumours are angiogenic, while their RHGP counterparts are vessel co-opting. The patients with DHGP tumours have a better response to anti-angiogenic agents and chemotherapy, as well as the prognosis. To determine the influence of vitamin D supplementation in CRCLM, we analyzed the HGPs and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It has been reported that CRCLM patients with vessel co-opting RHGP tumours have the worst prognosis [ 8 , 47 ]. The lack of angiogenic vascularization in vessel co-option tumours is linked to their resistance to antiangiogenic agents, such as Bevacizumab [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CRCLM patients with vessel co-opting RHGP tumours have the worst prognosis [ 8 , 47 ]. The lack of angiogenic vascularization in vessel co-option tumours is linked to their resistance to antiangiogenic agents, such as Bevacizumab [ 8 ].…”
Section: Discussionmentioning
confidence: 99%